SUPERVISI MANAJERIAL DALAM MENINGKATKAN MUTU LEMBAGA PENDIDIKAN ISLAM - FAKHRIAH FAKHRIAH (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2022)
This paper aims to describe the importance of managerial supervision, to determine the objectives of managerial supervision and the principles of managerial supervision in improving the quality of Islamic educational institutions. This research is a type of library research with a qualitative approach. Sources of data used are secondary data sources, namely in the form of books and articles relevant to this research. Collecting data through documentation by exploring the meaning and information or empirical data obtained from books and scientific research results and other literature with the aim of wanting to know more about managerial supervision that can be done to improve the quality of Islamic educational institutions. The results of the study indicate that managerial supervision is very much needed in Islamic educational institutions. Managerial supervision is not related to a single subject matter, but involves all aspects of the structure and management of the school. The quality of Islamic educational institutions is not only seen from the success of students and teachers, but all components in the school determine the quality of Islamic educational institutions. Managerial supervision is one way to improve the quality of Islamic educational institutions, because with supervision, guidance and assessment from supervisors, it will be able to increase productivity and management performance at Islamic educational institutions, and in the end will be able to improve the quality of education. ABSTRAKTulisan ini bertujuan untuk mendeskripsikan pentingnya supervisi manajerial, untuk mengetahui sasaran supervisi manajerial dan prinsip-prinsip supervisi manajerial dalam meningkatkan mutu lembaga pendidikan Islam. Penelitian merupakan jenis riset kepustakaan (library research) dengan pendekatan kualitatif. Sumber data yang digunakan adalah sumber data sekunder, yaitu berupa buku-buku dan arikel yang relevan dengan penelitian ini. Pengumpulan data melalui dokumentasi dengan menggali makna dan informasi atau data empirik yang didapat dari buku-buku dan hasil penelitian ilmiah maupun literatur yang lain dengan tujuan ingin mengetahui lebih banyak tentang supervisi manajerial yang dapat dilakukan untuk meningkatkan mutu lembaga pendidikan Islam. Hasil penelitian menunjukkan bahwa supervisi manajerial sangat diperlukan pada lembaga pendidikan Islam. Supervisi manajerial tidak berhubungan dengan satu pokok permasalahan saja, tetapi menyangkut semua aspek yang ada dalam struktur dan manajemen sekolah. Mutu lembaga pendidikan Islam tidak hanya dilihat dari keberhasilan siswa dan gurunya saja, tetapi seluruh komponen yang ada di sekolah ikut menentukan mutu lembaga pendidikan Islam. Supervisi manajerial merupakan salah satu cara untuk meningkatkan mutu lembaga pendidikan Islam, karena dengan adanya pengawasan, pembinaan dan penilaian dari supervisor, akan dapat meningkatkan produktivitas dan kinerja manajemen pada lembaga pendidikan Islam, dan pada akhirnya akan dapat meningkatkan mutu pendidikan.